Kids Those Days: Children in Medieval Culture
1 online resource.
Keywords: In Kids Those Days , Lahney Preston-Matto and Mary Valante have organized a collection of interdisciplinary research into childhood throughout the Middle Ages. Contributors to the volume investigate childhood from Greece to the "Celtic-Fringe," looking at how children lived, suffered, thrived, or died young. Scholars from myriad disciplines, from art and archaeology to history and literature, offer essays on abandonment and abuse, fosterage and guardianship, criminal behavior and child-rearing, child bishops and sainthood, disabilities and miracles, and a wide variety of other subjects related to medieval children. The volume focuses especially on children in the realms of religion, law, and vulnerabilities. Contributors are Paul A. Broyles, Sarah Croix, Gavin Fort, Sophia Germanidou, Danielle Griego, Máire Johnson, Daniel T. Kline, Jenni Kuuliala, Lahney Preston-Matto, Melissa Raine, Eve Salisbury, Ruth Salter, Bridgette Slavin, and Mary A. Valante.